2012
DOI: 10.5424/fs/2112211-02193
|View full text |Cite
|
Sign up to set email alerts
|

Biomass models to estimate carbon stocks for hardwood tree species

Abstract: To estimate forest carbon pools from forest inventories it is necessary to have biomass models or biomass expansion factors. In this study, tree biomass models were developed for the main hardwood forest species in Spain: Alnus glutinosa, Castanea sativa, Ceratonia siliqua, Eucalyptus globulus, Fagus sylvatica, Fraxinus angustifolia, Olea europaea var. sylvestris, Populus x euramericana, Quercus canariensis, Quercus faginea, Quercus ilex, Quercus pyrenaica and Quercus suber. Different tree biomass components w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
5
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 37 publications
6
82
5
2
Order By: Relevance
“…Both good and bad stool percentages of total below-ground biomass (table 9) differed greatly from the reference value reported by different authors for the average tree in high forest of approximately 25 % below-ground biomass (Abrahamson & Caswell, 1982;Agren & Ingestad, 1987;Gower et al, 1993;Alberto & Elvir, 2008). They were also very different from the percentages found for holm oak in high forest by other authors such as Montero et al (2005) in dehesa systems (65 % aerial -35 % roots) or by Ruiz-Peinado et al (2012) (62% aerial -38% roots). However, the values obtained in the present study are very similar to those previously found for the species in coppices (Gracia et al, 1997(Gracia et al, , 1999a(Gracia et al, , 2005.…”
Section: Discussioncontrasting
confidence: 51%
“…Both good and bad stool percentages of total below-ground biomass (table 9) differed greatly from the reference value reported by different authors for the average tree in high forest of approximately 25 % below-ground biomass (Abrahamson & Caswell, 1982;Agren & Ingestad, 1987;Gower et al, 1993;Alberto & Elvir, 2008). They were also very different from the percentages found for holm oak in high forest by other authors such as Montero et al (2005) in dehesa systems (65 % aerial -35 % roots) or by Ruiz-Peinado et al (2012) (62% aerial -38% roots). However, the values obtained in the present study are very similar to those previously found for the species in coppices (Gracia et al, 1997(Gracia et al, , 1999a(Gracia et al, , 2005.…”
Section: Discussioncontrasting
confidence: 51%
“…In a study conducted in the southeastern Spain, in reference to the Mediterranean shrubs, Almagro et al (2010) also estimated a mean root/shoot ratio of 0.84. Ruiz-Peinado et al (2012) reported root/shoot ratios equal to 0.32 for Q. ilex, 0.30 for Olea europaea, and 0.81 for Ceratonia siliqua. Some studies highlight the fact that the root/shoot ratio values of plant species typically related to the Mediterranean context seem to be largely superior to the ratio values of trees and forests.…”
Section: Discussionmentioning
confidence: 99%
“…Total number of trees sampled was 21. For each sample tree in each size category, according to Ruiz-Peinado et al [23], a 500-g sample was collected to measure moisture in the laboratory. These samples were oven-dried to constant weight at 105 C.…”
Section: Methodsmentioning
confidence: 99%